Glucose Control Influences Glomerular Filtration Rate and Its Prediction in Diabetic Subjects - Rigalleau, Vincent; Lasseur, Catherine; Raffaitin, Christelle; Perlemoine, Caroline; Barthe, Nicole; Chauveau, Philippe; Combe, Christian; Gin, Henri (Diabetes care, 2006)
Glucose Control Influences Glomerular Filtration Rate and Its Prediction in Diabetic Subjects Vincent Rigalleau , MD, PHD 1 2 , Catherine Lasseur , MD 1 3 , Christelle Raffaitin 1 2 , Caroline Perlemoine , MD 1 2 , Nicole Barthe , PHARMD 1 4 , Philippe Chauveau , MD 1 3 , Christian Combe , MD, PHD 1 3 and Henri Gin , MD, PHD 1 2 1 Université de Bordeaux 2, Victor Segalen, Bordeaux, France 2 Department of Nutrition and Diabetes, Hôpital Haut-Lévêque, Pessac, France 3 Department of Nephrology, Hôpital Pellegrin, Bordeaux, France 4 Department of Nuclear Medicine, Hôpital Pellegrin, Bordeaux, France Address correspondence and reprint requests to Vincent Rigalleau, Nutrition-Diabétologie, Hôpital Haut-Lévêque, Avenue de Magellan, 33600 Pessac, France. E-mail: vincent.rigalleauatwanadoo.fr Abstract OBJECTIVE —Hyperglycemia increases glomerular filtration rate (GFR), but the influence of HbA 1c (A1C) on GFR and GFR’s prediction by recommended equations remains to be determined. RESEARCH DESIGN AND METHODS —In 193 diabetic patients, we searched for an association between A1C and isotopically measured GFR (51Cr-EDTA) and their predictions by the Cockcroft and Gault formula (CG) and the modification of diet in renal disease (MDRD) equation. Their accuracy for the diagnosis of moderate (GFR <60 ml/min per 1.73 m 2 ) or severe (GFR <30 ml/min per 1.73 m 2 ) renal failure was compared from receiver operating characteristic (ROC) curves, before and after categorizing the patients as well (A1C ≤8%) or poorly controlled. RESULTS —The mean GFR was 57.0 ± 34.8 ml/min per 1.73 m 2 and was well correlated with both estimations (CG r = 0.75, MDRD r = 0.83; P < 0.05). The areas under the ROC curves were higher with the MDRD ( P < 0.05). A1C was correlated ( P < 0.001) with the GFR ( r = 0.29), MDRD ( r = 0.38), CG ( r = 0.26), and the absolute differences between the GFR and their CG but not MDRD estimations ( r = 0.17, P < 0.05). Each +1% A1C was associated with +6.0 ml/min per 1.73 m 2 GFR (CG +5.6, MDRD +5.3). After separating well-controlled ( n = 88, A1C 7.0 ± 0.7%) and poorly controlled ( n = 105, 9.6 ± 1.3%) patients, the diagnostic accuracies were better ( P < 0.05) for the MDRD, except for the diagnosis of moderate renal failure in well-controlled patients (NS). CONCLUSIONS —GFR and its estimations correlate with A1C. Although the relations between GFR and its estimations were not affected by the degree of glucose control, the precision and diagnostic accuracy of the CG formula were diminished for A1C >8%. The MDRD equation was more accurate and robust in diabetic patients with impaired renal function. CG, Cockcroft and Gault formula GFR, glomerular filtration rate MDRD, modification of diet in renal disease ROC, receiver operating characteristic Footnotes A table elsewhere in this issue shows conventional and Système International (SI) units and conversion factors for many substances. The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C Section 1734 solely to indicate this fact. Accepted March 30, 2006. Received February 21, 2006. DIABETES CARE